جدلية العلاقة بين العقل والوحي من منظور حنفي وأبو زيد - Lamloum, Fatma Mohamed Abdoulla; Abdull Rahman Mahmood,; Muhamad Razak Idris, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
Islamic religious message has come to build a human life intellectually, ideologically, and culturally based on a solid foundation. It took the messengers and prophets responsible for this divine message to be published for all people. This religion has not emerged from intellectual and philosophical jurisprudence only, it has emerged from two sources of knowledge. Al-Najjar has referred to these sources of knowledge are revelation and reason, and it took the mind and the senses as means of its realization. Revealation is considered to be the most reliable source of knowledge that human receives from the holy Quran. The holy Quran considered intellect as the main source of knowledge and takes the responsibility of commissioning, forethought and argument. Both the reason and revealation according to Islamic approach are compatible and not conflicting. Their relationship is not a debatable relation, but the intellect is a mean to understand the revealation and believe on it. Meanwhile the revealation is a mean of the advancement of the human reason and expand its capacity since the intellect calls the human being for the highest degree of humanitarian sanity. In order for human to reach these degrees, he must have sensible intellect and receiving knowledge, so the sensible intellect is the one who looks at the universe in order to meditate and understand without deviation, and the knowledge that human receives from the Holy Quran. Hassan Hanafi and Nasr Hamid Abu Zayd have violated this framework through their palaver of intellect.